Green Park Energy sebagai Strategi Inovatif Peningkatan Energi Terbarukan di Indonesia Berbasis Green Wakaf - Hardiansyah, Kiki; Kanthi Pawening Tyas; Qintar Alifah Ristiana; Risma; Tuti; Rumaisah Azizah Al Adawiyah (Badan Wakaf Indonesia, 2023)
This article aims to develop the concept of green park energy to provide alternative solutions for increasing renewable energy in Indonesia based on green waqf. The research method used is descriptive qualitative with a conceptual type of article. Green park energy is a program that aims to increase the capacity of renewable energy in Indonesia and a means of community recreation in the form of parks. The park will produce electrical energy due to the conversion of various renewable energy such as water flow, solar light, wind or wind movement, biomass energy, and supporting renewable energy derived from pressure into electrical energy and supporting energy such as cooking fuel and vehicle fuel. In its financing, this green project is supported by waqf funds. The park will produce electrical energy due to the conversion of various renewable energy such as water flow, solar light, wind or wind movement, biomass energy, and supporting renewable energy derived from pressure into electrical energy and supporting energy such as cooking fuel and vehicle fuel. In its financing, this green project is supported by waqf funds.